The Two Cultures of Academic Leadership (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
This essay explores faculty and administrative leadership culture in the context of the pandemic health crisis. Differences and opportunities for leadership collaboration are identified that can help American higher education adapt to and prosper from the intense pressures for change.